Impact of organic and inorganic fertilizers on the growth and yield of cabbage in Ghana - Asomah, S.; Paarechuga Anankware, J.; Remember Adjei, R. (International Journal of Horticultural Science, 2021)
A field experiment was conducted at Dormaa Ahenkro, Ghana, to determine the impact of inorganic and organic fertilizers on the growth and yield of cabbage. The experiment was laid in a randomized complete block design with three replications. The experiment treatment comprises of sole application of poultry manure (PM), NPK 15:15:5, the combined application of poultry manure and NPK fertilizer (PM+NPK) and the control (no fertilizer). Data was collected on the number of leaves, stem girth, plant height, head diameter, head weight and edible head weight. There was a significant difference (P